Estudio de factibilidad para la creación de una sucursal de la empresa Credi Loja en el Cantón Zumba de la provincia de Zamora Chinchipe. - Yanza Gordillo, Gabriela Lisseth (2022)
The present work was elaborated under the objective of conducting a "Feasibility study for the creation of a branch of the company Credi Loja in the Zumba Canton of the province of Zamora Chinchipe". For the development of this study various methods were used which helped to find timely and real data, among them: the scientific method, inductive, deductive and analytical method, as well as appropriate techniques and tools such as direct observation and survey were used which helped to execute the market study, technical, legal and economic-financial study, where the financial evaluation indicators such as NPV, IRR, RBC, PRI and sensitivity analysis were applied. Finally, as a result, the location of the new branch was established in the downtown area of Zumba and through the financial-economic study and analysis of the indicators, the result was a positive NPV of $767. 571.93, an IRR of 55.25% which is higher than the opportunity rate of 11.08%, the RBC determined that for every dollar invested a profit of 0.12 dollars will be obtained, it also indicates that the investment will be recovered during 13 months of useful life of the company; therefore, it is concluded that the investment study is feasible to implement, since it would be of great importance because it would contribute significantly to the social and economic development of the Zumba canton. Key words: investment, market, budget, project, branch office.